Comparative phylogeographic patterns and processes of the incipient brown seaweeds Sargassum polycystum and S. plagiophyllum around the Thai-Malay Peninsula - Zhang, Tong-Yun; Wang, Qi-Qi; Sun, Zhong-Min; Draisma, Stefano G. A.; Hu, Zi-Min (Frontiers in Plant Science, 2025)
Incipient (recently-evolved) species are morphologically distinct and have a relatively short evolutionary history from a common ancestor, yet comparative phylogeographic patterns of incipient seaweed species have seldom been explored. Here, we created 339 mitochondrial cox1, 339 cox3, 339 cox1+cox3 and 286 nuclear ITS2 sequences for Sargassum plagiophyllum (10 populations) and 326 cox1, 336 cox3, 310 cox1+cox3 and 341 ITS2 sequences for S. polycystum (14 populations) around the Thai-Malay Peninsula (TMP), with the aim to explore potential drivers in shaping population genetic structuring and diversity over space, including a phylogeographic signature of incipient speciation. Comparative analysis showed that the two Sargassum species around the TMP diverged from their most recent common ancestor at c. 0.17 Mya, followed by a demographic expansion at c. 0.015–0.060 Mya. Oceanic currents drove contemporary continuous south-to-north gene flow in the Malacca Strait, leading to most genetic variation partitioned within populations and among populations within groups. Interestingly, the incipient S. polycystum and S. plagiophyllum shared their most common haplotypes/ribotypes, and mitochondrial datasets revealed much higher phylogeographic diversity in S. polycystum than in S. plagiophyllum. These results imply that the late Quaternary sea-level fluctuations and contemporary oceanic currents co-contributed to population genetic structuring and demographic histories of S. polycystum and S. plagiophyllum around the TMP. Importantly, comparative phylogeographic analysis of S. polycystum and S. plagiophyllum shed lights on the existence of a few separate late Pleistocene glacial refugia, such as the Andaman Sea for S. plagiophyllum and the northern Malacca Strait for S. polycystum, particularly the revealing of important signatures of their incipient speciation.